2018
DOI: 10.14512/gaia.27.s1.6
|View full text |Cite
|
Sign up to set email alerts
|

How Much of the Real-World Laboratory Is Hidden in Current Transdisciplinary Research?

Abstract: The concept of real-world laboratories is difficult to distinguish from the concept of transdisciplinary research. Thus, the question has arisen: to what extent is the real-world laboratory truly novel? If transdisciplinary research is considered a process providing only socially robust knowledge and orientation (instead of solutions), then the real-world lab could be thought of as a model in which evidence-supported solutions can be tested and adjusted, and progress can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…RwLs enable a transdisciplinary research practice that aims to contribute to societal change towards sustainability as well as identifying successful transformation strategies that may be transferred to other contexts. The current discourse explores how to integrate RwLs into an overarching conceptual understanding of the ideal-typical transdisciplinary research process (Jahn and Keil 2016;Ukowitz 2017;Rogga and Zscheischler 2018;Wanner et al 2018). Some authors see RwLs as places to implement previously well-researched sustainability innovations (Jahn and Keil 2016) or to test "knowledge and possible solutions resulting from a preceding TDR process" (Rogga and Zscheischler 2018).…”
Section: Rwls As Experimental Path Of Transdisciplinary Research: Stamentioning
confidence: 99%
“…RwLs enable a transdisciplinary research practice that aims to contribute to societal change towards sustainability as well as identifying successful transformation strategies that may be transferred to other contexts. The current discourse explores how to integrate RwLs into an overarching conceptual understanding of the ideal-typical transdisciplinary research process (Jahn and Keil 2016;Ukowitz 2017;Rogga and Zscheischler 2018;Wanner et al 2018). Some authors see RwLs as places to implement previously well-researched sustainability innovations (Jahn and Keil 2016) or to test "knowledge and possible solutions resulting from a preceding TDR process" (Rogga and Zscheischler 2018).…”
Section: Rwls As Experimental Path Of Transdisciplinary Research: Stamentioning
confidence: 99%
“…This also means critically analysing political-economic interventions and configurations that are associated with innovation and prevailing techno-optimism in society (Markusson et al, 2017;Pfotenhauer et al, 2019). Additionally, politics should recognize the possibility of transdisciplinary research to stimulate social learning and contribute to social justice in agricultural innovation and decision-making by applying contributive justice concepts and thus further supporting transformative research processes (see also Rogga et al, 2018). Not least, such development will also necessitate the political will to take up the results in a suitable format and move beyond the instrumental value of public participation for the sake of acceptance of decisions (Stilgoe & Guston, 2017).…”
Section: Science Has the Obligation And Responsibility To Think Of More Radical Solutionsmentioning
confidence: 99%
“…The combination of transdisciplinary processes with real-world lab approaches has already been observed in other studies (Rogga et al 2018). It has been shown that embedding the innovation process in a broader transdisciplinary discourse is conductive to estimating unintended effects more effectively, and reducing ethical concerns, but also to considering critical questions of legitimacy.…”
Section: Thesis #2 Slm Innovation Processes Follow a Multiple-objectimentioning
confidence: 69%
“…Transdisciplinary processes were also conducted, as well as very incremental management approaches that can be described as "muddling through". Combinations of several approaches, such as a transdisciplinary learning process with a real-world lab approach (see also Rogga et al 2018) were often observed.…”
Section: Steering Innovation Processesmentioning
confidence: 99%